Analisis Kinerja Penjualan Risoles Melalui Program Kreativitas Mahasiswa Kewirausahaan (PKM-K) - Septy, Rosana Nabila; Hapsari, Dinda Tri; Mayrawanti, Nur Afifah Eka; Al Kautsarrani, Digma Lailil; Al’fiyah, Nur (PUTRA JAWA PUBLISHER, 2024)
This research is an in-depth analysis of the effectiveness of digital marketing strategies as a key instrument in increasing sales of risoles, particularly within the framework of the Student Creativity Program (PKM-K). The main focus of this research is to identify and evaluate the impact of the PKM-K program's contribution to increasing the visibility and consumer acceptance of risoles products. The research method applied involved careful analysis of sales data, including revenue results and total sales of risoles of each variant, with particular emphasis on exploring and implementing digital marketing strategies that support the promotion and distribution of Risol Hap risoles. The findings of this study reveal that the PKM-K program plays a significant role in opening up new opportunities for increased sales, and that digital marketing is an effective catalyst in reaching and building relationships with the target market. The word